The Potential Explanatory Role of Perceived Stress in Associations Between Subjective Social Status and Health-Related Quality of Life Among Homeless Smokers. (January 2016) - Garey, Lorra; Reitzel, Lorraine R.; Kendzor, Darla E.; Businelle, Michael S.
Homeless individuals smoke at high rates relative to the general population and are at heightened risk of tobacco-related illnesses and poor health-related quality of life (HRQoL). Homeless smokers also report low subjective social status (SSS) or perceived social standing relative to others. SSS may contribute to poor HRQoL, potentially through perceived stress. The current study examined the role of perceived stress in the association of SSS and HRQoL among 227 (70.9% male, M age = 43.2) homeless smokers. Participants completed self-report measures of SSS, perceived stress, and HRQoL. Perceived stress partially explained the relation between SSS (United States and Community) and HRQoL in covariate-adjusted analyses. Results suggested that perceived stress is a pathway through which SSS contributes to HRQoL among homeless smokers. Findings broaden current understanding of the impact of social disadvantage and perceived stress on HRQoL among homeless smokers.